2019
DOI: 10.2196/12945
|View full text |Cite
|
Sign up to set email alerts
|

Digital Problem-Based Learning in Health Professions: Systematic Review and Meta-Analysis by the Digital Health Education Collaboration

Abstract: BackgroundThe use of digital education in problem-based learning, or digital problem-based learning (DPBL), is increasingly employed in health professions education. DPBL includes purely digitally delivered as well as blended problem-based learning, wherein digital and face-to-face learning are combined.ObjectiveThe aim of this review is to evaluate the effectiveness of DPBL in improving health professionals’ knowledge, skills, attitudes, and satisfaction.MethodsWe used the gold-standard Cochrane methods to co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
75
1
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(89 citation statements)
references
References 43 publications
3
75
1
10
Order By: Relevance
“…The findings reinforce PBL's position as innovative learning which has been reported to be able to optimize learning processes (Dring, 2019;Movahedzadeh, Patwell, Rieker, & Gonzalez, 2012;Yew & Goh, 2016) and outcomes (Mundilarto & Ismoyo, 2012;Zejnilagić-Hajrić, Šabeta, & Nuić, 2015). The combination of PBL with online learning in this study is also in line with previous research which also informs about an increase in science learning when blended-PBL is implemented in learning (Ammann, Vignoli, & Kaap-Fröhlich, 2019;Car et al, 2019).…”
supporting
confidence: 89%
“…The findings reinforce PBL's position as innovative learning which has been reported to be able to optimize learning processes (Dring, 2019;Movahedzadeh, Patwell, Rieker, & Gonzalez, 2012;Yew & Goh, 2016) and outcomes (Mundilarto & Ismoyo, 2012;Zejnilagić-Hajrić, Šabeta, & Nuić, 2015). The combination of PBL with online learning in this study is also in line with previous research which also informs about an increase in science learning when blended-PBL is implemented in learning (Ammann, Vignoli, & Kaap-Fröhlich, 2019;Car et al, 2019).…”
supporting
confidence: 89%
“…A systematic review of randomized controlled trials concluded that digital problem-based learning (DPBL) was potentially more effective in improving knowledge and skills than traditional problem-based learning (PBL) due to greater student interaction and engagement in DPBL [ 8 ]. However, the review found mixed data concerning student satisfaction outcomes [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review of randomized controlled trials concluded that digital problem-based learning (DPBL) was potentially more effective in improving knowledge and skills than traditional problem-based learning (PBL) due to greater student interaction and engagement in DPBL [ 8 ]. However, the review found mixed data concerning student satisfaction outcomes [ 8 ]. Various studies on student satisfaction with online learning have identified the following factors: instructor interaction, communication, active learning, students’ ability to initiate and control their actions in the learning environment, efficient assessment of academic progress, technology, and the learning environment [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of PBL is more efficient when the combination is carried out (Ammann, Vignoli, & Kaap-Fröhlich, 2019). The results of the meta-analysis also inform that blended-PBL is more effective than traditional PBL (Car et al, 2019). Blended-PBL was also reported to be more effective in creating active learning in Asian students (Shimizu, Nakazawa, Sato, Wolfhagen, & Könings, 2019).…”
Section: Introductionmentioning
confidence: 77%
“…In the Biology Education field, research subjects in previous reports also often use high school students (Suwono & Dewi, 2019). Whereas various studies in higher education examining blended-PBL implementation often involve medical students (Car et al, 2019) or health (Ammann et al, 2019;de Jong, Krumeich, & Verstegen, 2017). In addition to the limitations of the research subject, the competencies analyzed in the various studies are also limited to students' scientific motivation and communication (Suwono & Dewi, 2019) and the mastery of knowledge (Car et al, 2019;Shimizu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%